The First Radio Astronomical Observation of Jupiter Radio Bursts in Malaysia - Abidin, Z.Z.; Ibrahim, Z.A.; Hamdan, H.; Asarani, A.T.M. (2006)
In this research note, the first radio astronomical observation of the Jupiter in Malaysia is presented. In Malaysia and in terms of foregrounds, radio observation is an excellent alternative to optical observation to detect extra-terrestrial objects. Clouds and rains do not effect sky's radio measurements. However, the main obstacle is the Radio Frequency Interferences (RFI), especially man-made. Thus careful choice of observing sites is important. The work in this paper shows results of observations at University of Malaya, which is deemed to be a sufficient, but by far not the best site for Jupiter tracking in Malaysia. A Yagi antenna is used for RFIs measurements and a dipole antenna is used for transit tracking of radio Jupiter. Two detections of radio Jupiter bursts and one solar radio burst detection are reported.